On the Priority of the Aristotelian Polis over the Individual The Polis as a Hylomorphic Whole - Panayides, Christos (Problemos, 2024)
In Politics I 2 (1253a18–27), Aristotle makes a controversial claim that the polis is prior in nature to the individual. The aim of this article is to reconstruct this thesis. According to recent scholarship, there are two main ways to understand priority in nature in Aristotle. It may be construed as ‘existential priority, or as ‘priority in being’. It is argued that: (a) The first option is problematic; it cannot give us a viable reading of the thesis in Politics I 2. Whereas (b) The second option provides us with a sound approach to the puzzle at hand. Furthermore, it is argued that the exegetical plausibility of the suggested reading of the thesis in Politics I 2 (1253a18–27) may be bolstered if we note that, for Aristotle, the polis is a particular kind of hylomorphic whole.
Keywords: Aristotle; Polis; Existential Priority; Priority in Being; Hylomorphism